Perceived stress and sleep quality among patients visiting primary and community health centres in Kerala: COVID-19 pandemic context - Thachorath, Abdul Rasik; Kalliyil, Fathimathul Jusna; Koorankot, Jaseem (International Journal Of Community Medicine And Public Health, 2024)
Background: The quality of sleep, a multifaceted construct encompassing factors such as duration, continuity, and depth, plays a pivotal role in cognitive function, while perceived stress, the subjective appraisal of stressors and one's ability to cope with them, has been identified as a significant factor affecting various aspects of individuals' lives. The present study aimed to investigate “Perceived stress and sleep quality among patients who visited community and primary health centers in Kerala during the COVID-19 pandemic”. Methods: The sample of the study consist of 60 patients aged between 18 and 50, who visited community and primary health centers in Kerala. Questionnaire for Perceived Stress Scale – Malayalam Version and Sleep Quality Scale were used in this study. Results: Findings of the study reveals that the patients visiting community and primary health centers in Kerala during the COVID-19 pandemic experience slightly elevated levels of perceived stress, closely aligned with general stress scores. However, their sleep quality remains largely normal, with only minor deviations. Conclusions: The study reveals a negative impact of pandemic-related stress on sleep timing and quality among these patients. Consequently, it underscores the importance of addressing both stress levels and sleep quality during such public health crises.